2021
DOI: 10.3389/fphar.2020.630825
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Ginsenoside Rg3 Combined with First-line Chemotherapy in the Treatment of Advanced Non-Small Cell Lung Cancer in China: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: Background: For advanced non-small cell lung cancer (NSCLC) patients, first-line chemotherapy is the main treatment in the clinic despite its efficacy is limited and adverse effects are always inescapable. Ginsenoside Rg3, an anti-cancer active ingredient by suppressing angiogenesis, has been increasingly widely used as an adjuvant in first-line chemotherapy for advanced NSCLC to optimize treatment in China. However, no comprehensive meta-analyses have been conducted to estimate the efficacy and safety of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Administration of GRg3 tablet (20 mg twice daily for 30 days) combined with gemcitabine and cisplatin in patients with advanced esophageal cancer increased the one-year survival rate and reduced drug-associated adverse events [ 15 , 17 ]. Meta-analysis of 20 clinical studies involving GRg3 (20 mg twice daily 6–24 weeks) combined with non-small cell lung cancer therapeutics indicated that Rg3 enhances short-term efficacy, prolongs overall survival rate, and reduces treatment-related toxicity [ 14 , 18 , 19 , 20 ]. Plasma exposure of GRg3 was increased 7.3-fold over the 6-fold dose range (10–60 mg, intramuscular injection) without a significant change in clearance and volume of distribution in Chinese healthy volunteers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Administration of GRg3 tablet (20 mg twice daily for 30 days) combined with gemcitabine and cisplatin in patients with advanced esophageal cancer increased the one-year survival rate and reduced drug-associated adverse events [ 15 , 17 ]. Meta-analysis of 20 clinical studies involving GRg3 (20 mg twice daily 6–24 weeks) combined with non-small cell lung cancer therapeutics indicated that Rg3 enhances short-term efficacy, prolongs overall survival rate, and reduces treatment-related toxicity [ 14 , 18 , 19 , 20 ]. Plasma exposure of GRg3 was increased 7.3-fold over the 6-fold dose range (10–60 mg, intramuscular injection) without a significant change in clearance and volume of distribution in Chinese healthy volunteers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2018) suggested that curcumin enhanced the activity of PTEN by down-regulating miR-21 and prevented the activity of the PI3K/AKT signaling which in turn inhibited the biological activity of GC cells. Ginsenoside Rg3, a steroidal saponin derived from Panax Ginseng in traditional Chinese medicine, has been found to have anti-tumor activity including promoting cytotoxicity of chemotherapy in various types of human cancers ( Tian et al, 2016 ; Yuan et al, 2017 ; Peng et al, 2020 ). Ginsenoside Rg3 can enhance the sensitivity to chemotherapy when used in combination with cisplatin ( Lee et al, 2014 ) or docetaxel ( Kim et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1996, some researchers conducted toxicological tests on Rg3, and the results showed that continuous administration of Rg3 had no obvious embryonic toxicity and teratogenicity, no obvious toxic reaction and no mutagenicity in rats. Relevant studies have reported that Rg3 combined with first-line chemotherapy improved efficacy of chemotherapy and reduced toxicity of chemotherapy drugs [21].…”
Section: Discussionmentioning
confidence: 99%